(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This article, using the example of Kashkadarya region, is devoted to forming ecological culture in school-age children. It teaches children to view nature as a part of themselves and of people, to have proper attitudes toward the natural resources they use and the surrounding environment, and to love, respect, and protect nature.